2003
DOI: 10.2460/ajvr.2003.64.708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of β3-adrenoceptor-mediated relaxation in intact and endotoxin-treated equine digital veins

Abstract: Beta3-adrenoceptors are functionally expressed in EDVs. Incubation in the presence of endotoxin, used as an in vitro model of laminitis, induced an alteration of beta-AR-mediated relaxations in EDVs, which could be the consequence of cyclooxygenase induction and subsequent prostanoid production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…coronary arteries and cerebral arteries) (Brawley et al, 2000). Recently, several in vivo and in vitro studies have demonstrated the functional expression of b 3 -AR in some vascular tissues (Gauthier et al, 2000;Mallem et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…coronary arteries and cerebral arteries) (Brawley et al, 2000). Recently, several in vivo and in vitro studies have demonstrated the functional expression of b 3 -AR in some vascular tissues (Gauthier et al, 2000;Mallem et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant effect demonstrated in this study could be relevant in the prevention of these pathologies where ROS are implicated. Recently, some authors have shown that ROS were implicated in the endotoxin‐induced impairment of β‐adrenoceptor‐mediated vasodilation in equine digital veins (Mallem et al. , 2003, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effect demonstrated in this study could be relevant in the prevention of these pathologies where ROS are implicated. Recently, some authors have shown that ROS were implicated in the endotoxin-induced impairment of b-adrenoceptor-mediated vasodilation in equine digital veins (Mallem et al, 2003(Mallem et al, , 2006. In agreement with these authors, our results suggest a synergistic effect of vasodilator and antioxidant properties of ACP that could be beneficial for the treatment of laminitis in horses.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, we currently carry out experiments on b-adrenoceptor activation, which mediates a concentrationdependent relaxation in rat, guinea-pig and equine isolated blood vessels. [6][7][8][9] To illustrate the use of nlme models, we chose the data obtained in a study of b-adrenoceptor-mediated effects in rat isolated thoracic aorta rings. [9] The experiments were performed in 12-week-old male Wistar Kyoto (WKY) rats.…”
Section: Experimental Designmentioning
confidence: 99%